2022
DOI: 10.1111/mcn.13343
|View full text |Cite
|
Sign up to set email alerts
|

Diet and food insecurity among mothers, infants, and young children in Peru before and during COVID‐19: A panel survey

Abstract: The COVID‐19 pandemic may impact diet and nutrition through increased household food insecurity, lack of access to health services, and poorer quality diets. The primary aim of this study is to assess the impact of the pandemic on dietary outcomes of mothers and their infants and young children (IYC) in low‐income urban areas of Peru. We conducted a panel study, with one survey prepandemic ( n = 244) and one survey 9 months after the onset of COVID‐19 ( n = 254). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
3
16
0
2
Order By: Relevance
“…The publications date from 2020 to 2022, with six cross-sectional articles ( 14 19 ) and four longitudinal articles ( 20 23 ). The studies were developed in different continents: America ( 14 , 16 19 , 23 ); Africa ( 14 ); Asia ( 15 , 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publications date from 2020 to 2022, with six cross-sectional articles ( 14 19 ) and four longitudinal articles ( 20 23 ). The studies were developed in different continents: America ( 14 , 16 19 , 23 ); Africa ( 14 ); Asia ( 15 , 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the sample, the studies evaluated pregnant women ( 15 , 17 , 19 ), pregnant and postpartum women ( 14 ), and mothers of children under 2 years of age ( 16 , 18 , 20 23 ). The sample number ranged from 68 ( 18 ) to 6,592 women ( 17 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of populations in other countries of the region show similar prevalence rates (34). Poverty, concern about unemployment and loss of income due to COVID-19 are the probable causes of the increase in food insecurity in Peruvian households (9). A national study showed that the country's positive economic growth from 2005 to 2015 was interrupted and even declined by 0.8% during the pandemic (10).…”
Section: Discussionmentioning
confidence: 99%
“…These prevalence rates of food insecurity in the country was worsened by the arrival of the pandemic. In a study of households in low-income urban areas of Peru, 46.9% of households experienced moderate household food insecurity and 4.1% experienced severe food insecurity (9). Unemployment and loss of income due to COVID-19 would be the probable causes of the increase in food insecurity in Peruvian households (10).…”
Section: Introductionmentioning
confidence: 99%
“…An observational study enrolling 1000 Spaniards with a mean age of 51 years reported that consumption of SSBs had increased in participants who gained weight during the COVID-19 lockdown, compared with those who did not gain weight (71.0% vs. 23.1%, p < 0.001) [ 154 ]; however, a COVID-19 health survey of 28,029 Belgian participants aged ≥ 18 years showed that consumption of SSBs increased both in participants who gained weight (9.2%) and in those who did not (8.7%) during the COVID-19 lockdown [ 155 ]. Data, obtained from Peruvian participants in the Perusano (pre-COVID-19) and the Stamina (COVID-19) surveys, showed a high prevalence of SSBs consumption in both populations (>78.0%) [ 156 ].…”
Section: Chronic High Intake Of Fructose and Its Potential Involvemen...mentioning
confidence: 99%